Media Gambar dalam Pembelajaran Kosakata Bahasa Arab - Baiq Tuhfatul Unsi (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2014)
Vocabulary is very important domiciled in speaking activities. In reading, speaking, writing, and listening to always use the vocabulary. Thus the minimal vocabulary that will be an obstacle in communication. Reality in schools, in general learning vocabulary in a way that is monotonous, the students were asked to interpret a vocabulary in the dictionary, and then memorize it. This is becoming one of the causes of learning is not maximal. Therefore, there needs to be an alternative vocabulary learning techniques and media. One is the media image to improve vocabulary mastery. Media images are very supportive of the students in the learning process, because media images would provide freedom for students to express, express and let out all the creativity and talent that there is in him.